2005
DOI: 10.1111/j.1365-2842.2005.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of stresses in simulated flared root canals subjected to various post–core applications

Abstract: Cervical root fracture is a major clinical problem in flared root canals treated with different post and core applications. This in vitro study evaluated the stress transfer of different post and core systems to the cervical part of the artificially created flared root canals, by using strain gauges. The post-core systems investigated were: (a) cast post-core system without resin reinforcement, (b) cast post-core system with resin reinforcement, (c) pre-fabricated post and resin core with resin reinforcement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 17 publications
2
51
0
6
Order By: Relevance
“…Experimental studies of cast post revealed that cast post demonstrated high incidence of catastrophic root fracture on fracture strength testing. Because of a marked difference in modulus of elasticity between cast post and dentin, however, it cannot reinforce root structure particularly in the case of thin-walled immature tooth 11) . EverStick � Post has comparable elastic modulus with dentin and can be customized in size by bonding to each other to adapt a large flared canal.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies of cast post revealed that cast post demonstrated high incidence of catastrophic root fracture on fracture strength testing. Because of a marked difference in modulus of elasticity between cast post and dentin, however, it cannot reinforce root structure particularly in the case of thin-walled immature tooth 11) . EverStick � Post has comparable elastic modulus with dentin and can be customized in size by bonding to each other to adapt a large flared canal.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that root reinforcement with composite resin in immature tooth improves fracture resistance 5,11) . Nevertheless, comparative studies of fiber post and titanium post in flared large canal reinforced with composite resin has not been published.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…In addition, the closer the conformance of the fibrous reinforcement is to the original structure, the better the stress transfer, and the lower the occurrence of residual stresses from shrinkage of the luting resin agent. [30][31] Although the preservation of the remaining tooth structure and restoration of a severely weakened endodontically-treated tooth have been evaluated in different clinical reports [26][27][28]32 and research articles, [33][34][35][36] based on the knowledge of the authors of the current study, no study has evaluated microleakage in overflared root canals restored with different fiber reinforced dowels.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber post sistemleri diş dokusu ile uyumlu mekanik özellikleri, estetik avantajları ve kullanım kolaylığı açısından sık tercih edilmektedir. Ancak özellikle karbon fiber postlar yüzeylerindeki düşük hidroxil iyonları nedeniyle diş dokusuna ve kor malzemesi olarak kullanılacak kompozite iyi bağlanamamakta ve bu zayıf bağlantı restorasyonda başarısızlığa neden olmaktadır 5 . Lityumdisilikat(IPS Press e-max) ile güçlendiri-lmiş cam seramik restorasyonlar yüksek estetik özellik-lerinden dolayı üst çene ön bölge dişlerinin lamine veneer veya tam seramik veneer ile restorasyonunda sıklıkla tercih edilmektedir.…”
Section: Introductionunclassified